ANALYSIS OF RECEIVABLES MANAGEMENT ON THE EFFECTIVENESS OF CASH FLOWS AT PORTS TANJUNG PRIOK BRANCH PANJANG - Rizkia, Aisyah; Destalia, Mediya; Harori, M. Iqbal (Jurnal Kompetitif Bisnis, 2023)
This study aims to describe the analysis of accounts receivable management on the effectiveness of cash flow at PT Pelabuhan Tanjung Priok Branch Panjang. This type of research is descriptive research using a qualitative approach. Sources of data in the research used are primary data and secondary data. Data collection techniques are observation, interviews, and documentation. The results showed that the management of receivables carried out by PT Pelabuhan Tanjung Priok Long Branch, namely collecting accounts receivable, conducting analysis of accounts receivable turnover (RTO) and collection of receivables (ACP), collecting trade receivables, confirming accounts receivable, making customer assessment standards using the method 5C, and provide credit terms to prospective borrowers. Based on the calculation results, it can be seen that the management of accounts receivable affects the company's cash flow. It can be seen that the results of the calculation of receivables turnover (RTO) have increased every year and the results of the calculation of collection of accounts receivable (ACP) have decreased every year which indicates that the faster the proceeds can be collected back into cash. In this case, cash inflows have increased due to payment of receivables from service users. So it can be concluded that wealth has a relationship with the company's cash flow.